1983
DOI: 10.3177/jnsv.29.447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soybean protein on coprostanol production and cholesterol metabolism in cholesterol-fed rats.

Abstract: SummaryThe effect of soybean protein on coprostanol production and cholesterol metabolism was studied in cholesterol-fed rats.Plasma cholesterol was decreased in the soybean protein diet group compared to the casein diet group. Although coprostanol was produced more in rats fed soybean protein than in those fed casein, no difference was observed in the levels of total neutral steroids at any part of the intestine.The activity of microbial conversion from cholesterol to coprostanol was evidently high in rats fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Many works have been concerned with mechanism(s) by which dietary proteins affect plasma cholesterol levels (13)(14)(15). Several lines of evidence suggest that fecal steroid excretion is one of the main factors that affect plasma cholesterol (5,(16)(17)(18)(19)(20), and we have also presented results which support this suggestion (21). In the present study, we further examined the relationship between plasma cho lesterol level and fecal steroid excretion in obese and normal mice.…”
Section: Discussionsupporting
confidence: 75%
“…Many works have been concerned with mechanism(s) by which dietary proteins affect plasma cholesterol levels (13)(14)(15). Several lines of evidence suggest that fecal steroid excretion is one of the main factors that affect plasma cholesterol (5,(16)(17)(18)(19)(20), and we have also presented results which support this suggestion (21). In the present study, we further examined the relationship between plasma cho lesterol level and fecal steroid excretion in obese and normal mice.…”
Section: Discussionsupporting
confidence: 75%
“…The formation of hyodeoxycho lic acid from cholic acid by microflora was also increased. The stimulation of coprostanol formation due to undigested soybean protein has been reported by other groups (5,28). The soybean protein used in the present study contained very little saponin (less than 4g/kg).…”
Section: Fecal Excretion Of Cholesterol and Its Metabolitessupporting
confidence: 53%
“…After absorption, further modi fication of the steroid may occur in the liver (89) . Research with steroid biotransformations by intestinal bacteria has emphasized the three major classes of steroids which pass through the GI tract; these are the bile acids (43,78,92,94,103), cholesterol (18,39,143,147), and steroid hormones (14,16,154). Although this review will almost exclusively deal with bacteria, it should be noted that protozoa and fungi can also play an important role in steroid biotransformations (21,60,121).…”
Section: Bacterial Transformations Of Steroids In the Gastrointestinamentioning
confidence: 99%
“…The net result would be an increased circulating bile acid pool size. Higher bile acid levels would also directly favor the absorption of cholesterol from the intestine(147).Tanaka et al(143) found that fecal bacteria from rats fed soy bean protein diets demonstrated an increased ability to produce coprostanol when compared to rats receiving casein as a protein source. The observed increase in biohydrogenation was attributed to soybean pro tein's ability to maintain higher levels of coprostanol-generating bac teria or bacteria with higher metabolic rats.…”
mentioning
confidence: 99%